Pengembangan Papan Gambar Emosi Sebagai Media Pengenalan Dan Pengelolaan Diri Anak Usia 5-6 Tahun - Wulan Fauzia; Kaenah Kaenah; Siti Nurkholifah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Self-regulation is a fundamental ability that needs to be developed in early childhood, particularly for children aged 5-6 years, as it is closely related to emotional awareness and readiness for formal learning environments. However, emotional regulation in early childhood is often not optimal because emotions are abstract concepts, while children at this age are still in the preoperational cognitive stage and require concrete and visual learning support. This study aimed to develop an Emotion Picture Board as a learning medium to help children recognize and manage their emotions appropriately. The research employed a Research and Development approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The product was developed based on children’s developmental needs and validated by experts in early childhood education, followed by classroom implementation with children aged 5-6 years. Data were collected through validation questionnaires, observation, and teacher interviews. The results showed that the Emotion Picture Board obtained a high level of validity and practicality, indicating that it is feasible for classroom use. Implementation results also demonstrated that the media effectively supported children in identifying emotions and practicing appropriate emotional responses. Therefore, the Emotion Picture Board can be considered an effective and child-friendly learning medium to support the development of emotional awareness and self-regulation in early childhood education.